2009
DOI: 10.1029/2009gl038727
|View full text |Cite
|
Sign up to set email alerts
|

Ice particle growth in the polar summer mesosphere: Formation time and equilibrium size

Abstract: [1] The growth kinetics for ice particles in the polar summer mesosphere is studied using the density of water vapor, temperature, and total ice volume simultaneously measured by the infrared Fourier Transform Spectrometer on the Atmospheric Chemistry Experiment (ACE-FTS) satellite. The results are based solely on the ACE-FTS retrievals, without using any adjustable parameters. The computed particle formation time is in the range between 2 hours at 150 K and 20 hours at 120 K, during which particles come to eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…Lidar measurements have shown that there are diurnal variations in the properties of PMCs [ Fiedler et al , 2005; Chu et al , 2006], which suggests that there is a significant diurnal variation in saturation. Recent studies show that the ice particles in PMCs form and develop on time scales of hours to a few days [ Rapp and Thomas , 2006; Zasetsky et al , 2009], hence PMCs are likely to be sensitive not just to the saturation conditions at the time of the measurement, but to the recent history of saturation conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Lidar measurements have shown that there are diurnal variations in the properties of PMCs [ Fiedler et al , 2005; Chu et al , 2006], which suggests that there is a significant diurnal variation in saturation. Recent studies show that the ice particles in PMCs form and develop on time scales of hours to a few days [ Rapp and Thomas , 2006; Zasetsky et al , 2009], hence PMCs are likely to be sensitive not just to the saturation conditions at the time of the measurement, but to the recent history of saturation conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The latter values are determined from the ice mass density under the assumption that particles have an effective radius of about 60 nm. As was described in our early publications [e.g., Zasetsky et al, 2009a;Zasetsky et al, 2009b;Petelina and Zasetsky, 2009], the ACE-FTS infrared spectra are sensitive to the volume of ice (or ice mass density), but not to the variations in the size of ice particles within the 10-100 nm range. Therefore, our assumption on the particle effective radius of 60 nm, based on the coincident data measured by a different satellite instrument as described by Eremenko et al [2005], does not affect the results presented in this work.…”
Section: Resultsmentioning
confidence: 79%
“…When ice particles grow to optically visible sizes, they are referred to as polar mesospheric clouds (PMCs) or noctilucent clouds (NLCs). These clouds are composed of water ice that originally nucleates near the mesopause, at the altitudes of 87 to 91 km [e.g., Rapp and Thomas , 2006; Zasetsky et al , 2009a], consequently grows at rates that are still poorly understood [e.g., von Zahn and Berger , 2003; Murray and Jensen , 2009; Zasetsky et al , 2009b] and sediments down to 80–82 km, where it evaporates, and forms a seasonally enhanced water vapor layer [e.g., Urban et al , 2007].…”
Section: Introductionmentioning
confidence: 99%
“…However, for accurate comparisons to models, both water vapour and temperature should ideally be measured simultaneously. Such measurements are less common, and have to date mainly been provided by solar occulting instruments such as HALOE (McHugh et al, 2003), ACE-FTS (Zasetsky et al, 2009) and AIM-SOFIE ). These measurements have been used in several studies (e.g.…”
Section: O M Christensen Et Al: Retrieval Of Water Vapour Around Pmentioning
confidence: 99%
“…These measurements have been used in several studies (e.g. Rong et al, 2012;Zasetsky et al, 2009) to investigate the relationship between the background atmosphere and PMCs.…”
Section: O M Christensen Et Al: Retrieval Of Water Vapour Around Pmentioning
confidence: 99%